The influence of large classes in the English language teaching-learning process in Ecuadorian high schools - Espinosa Rodríguez, Oscar Efrén (2014)
This research work analyzes the possible influence of the large classes in teaching-learning of English language in Ecuadorian high schools and the probable impact in the learning process. The teaching of English language in Ecuador has not given the expected results due to the students who finish secondary education do not achieve the basic language communicative competence. For this reason, this study tries to determine whether or not large classes affect the learning process. This project was conducted in Manta city, where UEEFAE No. 4 and Stella Maris high schools are located. The sample was a group of students who were chosen randomly, the participants belong to 8th, 9th, 10th and 3rd of senior high school courses respectively. The qualitative and quantitative methods were used to discover if the instructional, social, and psychological implications of large classes exist on teaching-learning process. Results and their discussion suggest that there is influence of large classes in the learning process. So, teachers should update teaching information to avoid that students will be influenced by those problems in the learning process in high schools.